Dynamic commercial lobbying - Thomas Groll; Christopher J. Ellis (Center for Economic Studies and ifo Institute (CESifo), 2013)
This study explains the observed repeated personal interactions between lobbyists and policymakers. The analysis uses a dynamic model of commercial lobbying in which citizens may hire lobbyists to present policy proposals on their behalf to policymakers. It is shown that repeated interactions with lobbyists simplify a policymaker's information problem in the presence of unverifiable information provision and allow a solution to their contracting problem. The welfare implications of these interactions depend on whether the policymakers' information or contracting problem predominates. Further, the policymaker's information problem and financial contributions may actually improve social welfare in comparison to the full information outcome.
Keywords: D72; D78; 330; dynamic lobbying; influence activities; information acquisition; financial contributions; commercial lobbying; political access; moral hazard